Zoning for ecosystem restoration based on ecological network in mountainous region. (September 2022) - Jiang, Hong; Peng, Jian; Zhao, Yanni; Xu, Dongmei; Dong, Jianquan
Graphical abstract: Highlights: An ecosystem restoration zoning framework based on ecological network is proposed. Differentiated ecosystem restoration strategies are proposed for ecological zones. Both ecological network and zoning show obvious east-west differentiation. Abstract: Ecological network is an important landscape approach for biodiversity and ecosystem conservation. However, the lack of further spatial analysis and ecological zoning makes it difficult to implement ecological conservation and restoration measures based on ecological network. In this study, we proposed a framework for ecological zoning based on ecological network with a case study in Yunnan Province, China. The results showed that the ecological network in the study area was consisted of ecological sources with the total area of 136496.56 km 2, 276 ecological corridors with an average length of 41.40 km, and pinchpoints and barriers with an area of 425.54 km 2 and 1422.83 km 2 respectively. Yunnan Province was divided into five ecological zones based on ecological network. Source protection zone included 153 watersheds, with large area and high connectivity of ecological sources, needing to conserve the original natural ecosystem. Source enhancement zone included 103 watersheds with ecological sources of small area and discrete distribution. Ecological conservation was particularly important in southeast karst regions. Corridor construction zone included 143 watersheds, needing to build dense ecological corridors in an orderly manner. Ecological node restoration zone included 15 watersheds. Key ecological nodes needed restoration to enhance the overall connectivity. Non-ecological network zone needed to be paid attention to local ecological conservation. The zoning framework based on ecological network can help to implement ecological conservation and restoration in light of local conditions.